Receptiveness Of Internet Banking By Malaysian Consumers: The Case Of Penang - T. Ramayah, T. Ramayah; Muhamad Jantan, Muhamad Jantan; Mohd Noor, Mohd Nasser; Koay, Pei Ling (Asian Academy of Management (AAM), 2003)
This is a study about Internet banking acceptance in Malaysia. Due to the impending liberalization, Malaysian banks are desperately embracing this new distribution channel to prepare themselves for the competition which is looming in the near future. Although the awareness level is high, this has not translated into actual use as only 23% have had some Internet banking experience. Security, availability of infrastructure and complexity of technology were main concerns reported by the respondents which is hindering the migration from traditional banking to Internet banking. In terms of external variables only prior experience and external pressure has been found to influence the intention to use. Perceived ease of use and perceived usefulness has been found to be significantly related to intention and perceived usefulness has been found to be a better predictor of intention to use compared to ease of use. In short it can be concluded that perceived usefulness is the driver of the intention to use Internet banking. The implications of this research is further explored.